2012
DOI: 10.1080/02699931.2011.579088
|View full text |Cite
|
Sign up to set email alerts
|

Counting to ten milliseconds: Low-anger, but not high-anger, individuals pause following negative evaluations

Abstract: Low-anger individuals are less reactive, both emotionally and behaviourally, to a large variety of situational primes to anger and aggression. Why this is so, from an affective processing perspective, has been largely conjectural. Four studies (total N=270) sought to link individual differences in anger to tendencies exhibited in basic affective processing tasks. On the basis of motivational factors and considerations, it was hypothesised that negative evaluations would differentially activate a psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Interestingly, studies that found evidence for reduced Pe amplitudes have been mostly conducted in impulsive violent patient samples, such as female incarcerated psychopaths (Maurer et al, 2015), violent offenders with psychopathy (Brazil et al, 2009), and impulsive-violent offenders (Chen et al, 2014). Error-processing deficits on the neurophysiological level in HTA individuals have not yet been investigated, even though there are reasons to expect that impaired error-processing may be present in high trait anger individuals as well (Robinson et al, 2012). Hence, to our knowledge this would be the first study to compare errorprocessing in HTA and LTA individuals on the neurophysiological level.…”
Section: Trait Anger and Error-processingmentioning
confidence: 99%
“…Interestingly, studies that found evidence for reduced Pe amplitudes have been mostly conducted in impulsive violent patient samples, such as female incarcerated psychopaths (Maurer et al, 2015), violent offenders with psychopathy (Brazil et al, 2009), and impulsive-violent offenders (Chen et al, 2014). Error-processing deficits on the neurophysiological level in HTA individuals have not yet been investigated, even though there are reasons to expect that impaired error-processing may be present in high trait anger individuals as well (Robinson et al, 2012). Hence, to our knowledge this would be the first study to compare errorprocessing in HTA and LTA individuals on the neurophysiological level.…”
Section: Trait Anger and Error-processingmentioning
confidence: 99%
“…Generally, trait anger is defined “in terms of individual differences in the disposition to perceive a wide range of situations as annoying or frustrating and by the tendency to respond to such situations with elevations in state anger” (Forgays et al, 1997 ). High levels of trait anger predict quite a few health outcomes (Robinson et al, 2012 ). For example, angry individuals suffer from excessive cardiovascular reactivity (Suarez et al, 1998 ), higher blood pressure (Suls et al, 1995 ), many other physical problems (Williams et al, 2002 ), and psychological health problems, such as borderline personality (Distel et al, 2012 ), attempted suicide (Daniel et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that the manipulation would prime approach behaviors primarily at high levels of trait anger. At low levels of trait anger, by contrast, the same provocations may prime avoidance as a sort of aggression-regulating strategy (Robinson, Wilkowski, Meier, Moeller, & Fetterman, 2012).…”
Section: Approach Motivation In Angermentioning
confidence: 99%